Development of e-module to improve students' science learning outcomes - Nur Indriani; Hamsu Abdul Gani; Arnidah Arnidah (Journal of Research in Instructional, 2026)
Today, teaching materials are not optimal for supporting students' conceptual understanding, and students easily become bored if the learning process is unengaging or monotonous, ultimately leading to low learning outcomes. This research aims to improve students' science learning outcomes by developing e-modules. The study followed the ADDIE research and development process. Individual trials involved 3 students, small-group trials involved 9 students, and implementation involved 30 students. Data were collected through observation, interviews, questionnaires, and tests. Data analysis included descriptions of interview results, calculations of student and teacher response percentages, pretest and posttest averages, and n-gain values. The results of the needs analysis show that teachers and students need science learning resources that they can use independently and can access flexibly. The average validation score for the material expert was 86%, and for media experts was 87%, indicating that the e-module was valid. The results of practicality tests with teachers and students showed that the e-module was practical for learning because it was easy to access and helped with understanding the material. The n-gain calculation showed a significant increase in students' science learning outcomes (n-gain = 0.72). The developed e-module met students' needs, was validated by experts, was practical to use, and effectively improved students' science learning outcomes. The e-module offered easy-to-access features, accurate information, and support for independent learning.